Trends and Problems in Merdeka Belajar Curriculum Research from 2018 to 2023: Bibliometric Analysis - Suhendri Suhendri; Afif Alfiyanto; Anne Rahayu; Wulan Sari; Budi Mardikawati (Universitas Muhammadiyah Enrekang, 2024)
This study conducted a bibliometric analysis of scientific publications on the Independent Learning Curriculum in Indonesia from 2018 to 2023. This curriculum was introduced to provide flexibility and autonomy in education, encouraging school creativity and innovation. Using bibliometric methods, the study identified a significant increase in publications since 2020, with most articles coming from Indonesia. Topical analysis highlights the main focus on curriculum implementation, its impact on learning outcomes, school and teacher readiness, and learning innovation. Frequently raised issues include limited resources in remote areas, lack of teacher training, and challenges in developing appropriate grading systems. Collaboration between researchers and institutions is also an important theme, showing joint efforts in understanding and developing the Independent Learning Curriculum. These findings are important for education policy and practitioners to improve the quality of curriculum implementation in the future, with recommendations to strengthen teacher training further and develop innovative assessment systems